Analysis of Guest Satisfaction Level in Increasing Guest Intend to Recommend at Renaissance Bali Uluwatu Resort & Spa - Dewi, Ni Kadek Sita Junika; Winia, I Nyoman; Suja, I Ketut; Septevany, Elvira (Journal of Business Management Education (JBME), 2022)
This study aims to determine the level of guest satisfaction and the efforts of Renaissance Bali Uluwatu Resort Spa in increasing guest's intend to recommend. As for implementing these objectives, the population in this study was guests who have stayed at the Renaissance Bali Uluwatu Resort Spa and the samples in this study were 50 survey e-mail using purposive sampling technique with descriptive statistical analysis techniques. The data used in this study is secondary data obtained from the results of the survey e-mail. The results obtained from this study are guests who intend to recommend have an average score of 8.7. It means that guests are very likely to recommend hotels, while the guest satisfaction variable has an average score of 9 which guests are very satisfied with the hotel. The efforts made by Renaissance Bali Uluwatu Resort Spa in increasing guest intent to recommend providing extraordinary services, lowering prices, providing facilities as offered, and simplifying the check-in process. The results show to increasing guests intend to recommend, Renaissance Bali Uluwatu Resort Spa makes satisfaction indicators as a standard for all staff so guests intend to recommend can be developed.